Clinical experience with F-fluorodeoxyglucose positron emission tomography and I-metaiodobenzylguanine scintigraphy in pediatric neuroblastoma: complementary roles in follow-up of patients - Tae Young Gil; Do Kyung Lee; Jung Min Lee; Eun Sun Yoo; Kyung-Ha Ryu (Korean Pediatric Society, 2014)
PurposeTo evaluate the potential utility of 123I-metaiodobenzylguanine (123I-MIBG) scintigraphy and 18F-fluorodeoxyglucose (18F-FDG) positron emission tomography (PET) for the detection of primary and metastatic lesions in pediatric neuroblastoma (NBL) patients, and to determine whether 18F-FDG PET is as beneficial as 123I-MIBG imaging.MethodsWe selected 8 NBL patients with significant residual mass after operation and who had paired 123I-MIBG and 18F-FDG PET images that were obtained during the follow-up. We retrospectively reviewed the clinical charts and the findings of 45 paired scans.ResultsBoth scans correlated relatively well with the disease status as determined by standard imaging modalities during follow-up; the overall concordance rates were 32/45 (71.1%) for primary tumor sites and 33/45 (73.3%) for bone-bone marrow (BM) metastatic sites. In detecting primary tumor sites, 123I-MIBG might be superior to 18F-FDG PET. The sensitivity of 123I-MIBG and 18F-FDG PET were 96.7% and 70.9%, respectively, and their specificity were 85.7% and 92.8%, respectively. 18F-FDG PET failed to detect 9 true NBL lesions in 45 follow-up scans (false negative rate, 29%) with positive 123I-MIBG. For bone-BM metastatic sites, the sensitivity of 123I-MIBG and 18F-FDG PET were 72.7% and 81.8%, respectively, and the specificity were 79.1% and 100%, respectively. 123I-MIBG scan showed higher false positivity (20.8%) than 18F-FDG PET (0%).Conclusion123I-MIBG is superior for delineating primary tumor sites, and 18F-FDG PET could aid in discriminating inconclusive findings on bony metastatic NBL. Both scans can be complementarily used to clearly determine discrepancies or inconclusive findings on primary or bone-BM metastatic NBL during follow-up.